Beginning ASP.NET 4.5 in C♯ - MacDonald, Matthew (The expert's voice in .NET, 2012)
This book explores ASP.NET, a core part of Microsoft's .NET Framework. It begins with the fundamentals: C# syntax, the basics of object-oriented programming, and the philosophy of the .NET Framework--